Pengembangan Kurikulum Berbasis Interpreneurship Di Sekolah / Madrasah - Angga Angga (IAIN Padangsidimpuan, 2019)
This article describes the development of entrepreneurship-based curricula in schools / madrasas. From the problems that are occurring in the form of an economic crisis and unemployment then requires the world of education to be a problem solver as an institution where the nation's generation is printed. In education there is a curriculum which is a guideline that not only formulates a goal to be achieved but also gives a lantern to clarify the direction of an educational process, thereafter an entrepreneurship based curriculum was developed. This curriculum is a concept of education aimed at creating cadres who will bring social change in community life and can find out what is needed by the community in developing their economy. The development of entrepreneurship based curricula is a challenge in facing the economic crisis as well as an opportunity to create young people not only ready to become laborers but able to open jobs.